CD4 Cell Counts at HIV Diagnosis among HIV Outpatient Study Participants, 2000–2009 - Kate Buchacz; Carl Armon; Frank J. Palella; Rose K. Baker; Ellen Tedaldi; Marcus D. Durham; John T. Brooks (AIDS Research and Treatment)
Background. It is unclear if CD4 cell counts at HIV diagnosis have improved over a 10-year period of expanded HIV testing in the USA. Methods. We studied HOPS participants diagnosed with HIV infection ≤6 months prior to entry into care during 2000–2009. We assessed the correlates of CD4 count <200 cells/mm3 at HIV diagnosis (late HIV diagnosis) by logistic regression. Results. Of 1,203 eligible patients, 936 (78%) had a CD4 count within 3 months after HIV diagnosis. Median CD4 count at HIV diagnosis was 299 cells/mm3 and did not significantly improve over time (P=0.13). Comparing periods 2000-2001 versus 2008-2009, respectively, 39% and 35% of patients had a late HIV diagnosis (P=0.34). Independent correlates of late HIV diagnosis were having an HIV risk other than being MSM, age ≥35 years at diagnosis, and being of nonwhite race/ethnicity. Conclusions. There is need for routine universal HIV testing to reduce the frequency of late HIV diagnosis and increase opportunity for patient- and potentially population-level benefits associated with early antiretroviral treatment.